Membangun Masyarakat Madani: Tinjauan Birokratik-Politik - Agus Dwiyanto (Magister Administrasi Publik, 1999)
Civil society would be evolved if the government and public bureaucracy can be changed so that it will be more conducive for independent institutions which are free from too much state interventions. Government intervention in societal economic and political activities should be minimized unless it will improve the efficiency and effectiveness of the society in fulfilling their needs. A civil society can be guaranteed if it has an all-inclusive government, one who can assure pluralism and accommodate diverse different groups. A more democratic public bureaucracy is also essential for developing a civil society. In effect, all citizens must be genuinely involved in governmental activities and public services through the governance bodies, referendum, polling or other mechanisms where they can control and influence public decision making process. Within the government, there must be redistribution of power so that check and balance among bureaucratic units can be maintained properly.